Pengembangan Intelektualitas melalui Literasi Membaca bagi Karang Taruna Desa Kota Daro II Kabupaten Ogan Ilir - Fera Widyanata; Deassy Apriani; Didik Susetyo; Abbas Effendi; M. Fajri Haidir; Harta Sinta (Jurnal Pemberdayaan Ekonomi, 2022)
Purpose: This community activity aims to increase literacy in reading interest in the younger generation of the Sriwijaya University fostered village, namely Kota Daro II Village, Rantau Panjang District, Ogan Ilir Regency. The selected target is youth members of the youth organization, which is about 20 to 30 people as the initiators of reading literacy in the community, especially children. This activity was carried out from August to October 2021 with several visits. Method: Carried out in stages including question and answer, introduction and empowerment. These stages are the pre-activity stage and the activity implementation stage. Result: This activity have an impact on increasing the enthusiasm and desire of service participants to get used to reading as well as being able to implement the importance of reading culture to the local community. It is hoped that it can foster interest in reading among children and youth of Kota Daro II.